2019
DOI: 10.3390/cells8070682
|View full text |Cite
|
Sign up to set email alerts
|

Identifying microRNAs and Their Editing Sites in Macaca mulatta

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that are critical in post-transcriptional regulation. Macaca mulatta is an important nonhuman primate that is often used in basic and translational researches. However, the annotation of miRNAs in Macaca mulatta is far from complete, and there are no reports of miRNA editing events in Macaca mulatta, although editing may affect the biogenesis or functions of the miRNAs. To improve miRNA annotation and to reveal editing events of miRNAs in Macaca mulatta, we generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 67 publications
6
10
0
Order By: Relevance
“…After statistical analysis of nucleotides besides these A-to-I editing sites, we found that the 5' and 3' end of these A-to-I editing sites preferred to be U and G (Fig. 2b), respectively, which was also noticed in previous studies 36,47,48,62 . As examples, MiRME maps of hsa-mir-1301 and hsa-mir-539 in one of the prefrontal cortex and frontal cortex samples (SRR1759213 and SRR2287868, respectively) were presented in Figs.…”
supporting
confidence: 84%
“…After statistical analysis of nucleotides besides these A-to-I editing sites, we found that the 5' and 3' end of these A-to-I editing sites preferred to be U and G (Fig. 2b), respectively, which was also noticed in previous studies 36,47,48,62 . As examples, MiRME maps of hsa-mir-1301 and hsa-mir-539 in one of the prefrontal cortex and frontal cortex samples (SRR1759213 and SRR2287868, respectively) were presented in Figs.…”
supporting
confidence: 84%
“…2a). Similar to previous results [3,4,17,18], the 5’ and 3’ side of these A-to-I editing sites preferred to be U and G, respectively (ED: Fig. 2b).…”
Section: Resultssupporting
confidence: 90%
“…3a and Table S2.5). Five of these 26 C-to-U editing sites are conserved in primates [18] (see ED: Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The angiopoietin (ANGPT) family is an important group of factors, specific for vascular endothelium, whose functions are mediated through two tyrosine kinase receptors, Tie1 and Tie2 [7]. The ANGPT-Tie ligand-receptor system exerts a key role in regulating vascular integrity [8,9].…”
Section: Introductionmentioning
confidence: 99%